Multi‐factor climate change effects on insect herbivore performance. Issue 6 (15th April 2013) - Scherber, Christoph; Gladbach, David J.; Stevnbak, Karen; Karsten, Rune Juelsborg; Schmidt, Inger Kappel; Michelsen, Anders; Albert, Kristian Rost; Larsen, Klaus Steenberg; Mikkelsen, Teis Nørgaard; Beier, Claus; Christensen, Søren
Abstract The impact of climate change on herbivorous insects can have far‐reaching consequences for ecosystem processes. However, experiments investigating the combined effects of multiple climate change drivers on herbivorous insects are scarce. We independently manipulated three climate change drivers (CO2, warming, drought) in a Danish heathland ecosystem. The experiment was established in 2005 as a full factorial split‐plot with 6 blocks × 2 levels of CO2 × 2 levels of warming × 2 levels of drought = 48 plots. In 2008, we exposed 432 larvae (n = 9 per plot) of the heather beetle (Lochmaea suturalis Thomson), an important herbivore on heather, to ambient versus elevated drought, temperature, and CO2 (plus all combinations) for 5 weeks. Larval weight and survival were highest under ambient conditions and decreased significantly with the number of climate change drivers. Weight was lowest under the drought treatment, and there was a three‐way interaction between time, CO2, and drought. Survival was lowest when drought, warming, and elevated CO2 were combined. Effects of climate change drivers depended on other co‐acting factors and were mediated by changes in plant secondary compounds, nitrogen, and water content. Overall, drought was the most important factor for this insect herbivore. Our study shows that weight and survival of insect herbivores may decline under future climate. The complexity of insect herbivore responses increases with the number of combined climate change drivers.